Brg1 and RUNX1 synergy in regulating TRPM4 channel in mouse cardiomyocytes - Tao Ban; Tao Ban; Tao Ban; Xianhui Dong; Ziyue Ma; Jing Jin; Jing Li; Yunfeng Cui; Yuyang Fu; Yongzhen Wang; Yadong Xue; Tingting Tong; et al. (Frontiers in Pharmacology)
BackgroundTransient Receptor Potential Melastatin 4 (TRPM4), a non-selective cation channel, plays a critical role in cardiac conduction abnormalities. Brg1, an ATP-dependent chromatin remodeler, is essential for regulating gene expression in both heart development and disease. Our previous studies demonstrated Brg1 impacted on cardiac sodium/potassium channels and electrophysiological stability, its influence on TRPM4 expression and function remained unexplored.MethodsWe investigated the role of Brg1 in regulating TRPM4 expression and function through overexpression and knockdown experiments in mouse cardiomyocytes and TRPM4-overexpressing HEK293 cells by western blot, qPCR, immunofluorescence staining and patch clamp techniques. Cardiomyocytes were exposed to hypoxia for 12 h to mimic cardiac stress, and Brg1 inhibition was performed to assess its impact on TRPM4 under hypoxia. Bioinformatic analyses (STRING and JASPAR databases), Co-immunoprecipitation (Co-IP), dual luciferase reporter assays, and Chromatin Immunoprecipitation (ChIP) were employed to study the interaction between Brg1, RUNX1, and TRPM4 transcription regulation.ResultsBrg1 positively regulated TRPM4 expression in mouse cardiomyocytes and modulated TRPM4 current in TRPM4-overexpressing HEK293 cells. Brg1 inhibition markedly diminishes TRPM4’s hyperexpression in cardiomyocytes exposed to hypoxia. Integrative analyses utilizing STRNG databases and Protein Data Bank unveiled a putative interaction between Brg1 and the transcription factor RUNX1, and we substantiated the interaction between Brg1 and RUNX1. Several binding sites of RUNX1 with the TRPM4 promoter region were predicted by the JASPAR database, and empirical validation substantiated Brg1 modulated TRPM4 promoter activity via RUNX1 engagement. ChIP confirmed that Brg1 interacted with RUNX1 forming a transcriptional complex that located in TRPM4 promoter.ConclusionOur study demonstrated that Brg1 and RUNX1 formed a transcriptional complex that modulated TRPM4 expression and function, especially under hypoxic conditions. These findings provided new insights into TRPM4 regulation and highlighted its potential as a therapeutic target for cardiac hypoxia-related disorders.